Characterization of aerobic oil and grease-degrading bacteria in wastewater. Issue 6 (19th March 2017) - Nzila, Alexis; Thukair, Assad; Sankara, Saravanan; Abdur Razzak, Shaikh
ABSTRACT: A bacterial consortium that degrades cooking oil (CO) has been isolated in wastewater (WW) samples, by enrichment in olive CO. This consortium could degrade 90% of CO within 7–9 days (from an initial 1% [w/v]), and it is more active at alkaline conditions. The 16S ribonucleic acid (RNA) gene analysis showed that it contains five bacterium species: Stenotrophomonas rhizophila, Sphingobacterium sp., Pseudomonas libanensis, Pseudomonas poae and Pseudomonas aeruginosa . This consortium can degrade the free fatty acids (FFA): palmitic, stearic, oleic, linoleic and linolenic acids; glycerol, glucose and amylose; and albumin, but could not efficiently degrade carboxymethyl-cellulose. Each strain could also degrade CO and FFAs. The level of bacterial crude-activity of extracellular lipases was found to be between 0.2 and 4U/ml. Using synthetic WW, the consortium could reduce 80% of the chemical oxygen demand [from 10550 ± 2828 mg/l], 80% of nitrogen (from 410 ± 78 mgl/l) and 57% of phosphorus (from 93 ± 25 mg/l). Thus, this consortium can be utilized in the removal of CO from WW.